Childhood in the late Ottoman Empire and after - Fortna, Benjamin C. (The Ottoman Empire and its Heritage, 2016)
This volume explores the variety of ways in which childhood was experienced, lived and remembered in the late Ottoman Empire and its successor states. The period of the late nineteenth and early twentieth centuries was a time of rapid change, and the history of childhood reflects the impact of new expectations, lived realities and national responsibilities on the youngest members of societies undergoing monumental change because of ideological, wartime and demographic shifts. Drawing on comparisons both within the Balkans, Turkey and the Arab lands and with Western Europe and beyond, the chapters investigate the many ways in which upheaval and change affected the youth. Particular attention is paid to changing conceptions of childhood, gender roles and newly dominant national imperatives. Contributors include: Elif Akşit, Laurence Brockliss, Nazan Çiçek, Alex Drace-Francis, Benjamin C. Fortna, Naoum Kaytchev, Duygu Köksal, Kathryn Libal, Nazan Maksudyan, Heidi Morrison, and Philipp Wirtz. This title, in its entirety, is available online in Open Access.